The impact of the Companions on managing Hajj seasons and services in the first century of the Hijri era - Albalawi, Shadia Abdulrahman (Journal of Humanities & Social Sciences, 2024)
This research aims to study the impact of the companions satisfied with Allah on the management of the Hajj seasons and services, where they had a great and unmistakable impact on us. The problem of the research is to reveal the efforts of the companions and their impact on the management of the Hajj seasons in the first century of Hijri, and to identify the impact they had. This research dealt with their management of the season by providing food security for pilgrims from the restaurant and the drink and digging wells for it and to hold workers accountable when attending the time of the season, separating liabilities and taking care of the season, Also, to subsidize people on pilgrimage and perform its functions, and their care to achieve security at the time of the season, especially with women, As well as their interest in achieving health security among pilgrims, and their distribution at the time of the season, Their care is to secure the roads leading to the pilgrimage in order to safeguard the safety of the pilgrims and sponsoring and expanding the successors to the two Holy Mosques, and conclude the talk of political speeches that were the time of the season.
Keywords: Management; Hajj Season; First Century AH